2015
DOI: 10.1186/s12917-015-0463-0
|View full text |Cite
|
Sign up to set email alerts
|

International Veterinary Epilepsy Task Force’s current understanding of idiopathic epilepsy of genetic or suspected genetic origin in purebred dogs

Abstract: Canine idiopathic epilepsy is a common neurological disease affecting both purebred and crossbred dogs. Various breed-specific cohort, epidemiological and genetic studies have been conducted to date, which all improved our knowledge and general understanding of canine idiopathic epilepsy, and in particular our knowledge of those breeds studied. However, these studies also frequently revealed differences between the investigated breeds with respect to clinical features, inheritance and prevalence rates. Awarene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
1
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(116 citation statements)
references
References 125 publications
(359 reference statements)
3
102
1
10
Order By: Relevance
“…We found that the prevalence of epilepsy was approximately 1.9 % in all dogs that presented to the teaching hospital (referrals only), and 0.9 and 0.4 % for IdE and StE, respectively. These percentages are similar to previous studies reporting 1–2.6 % for epilepsy in veterinary referral clinics, and 0.5–5 % for IdE in primary clinics [7]. These findings suggest that differences in breeds or countries are not associated with prevalence of epilepsy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found that the prevalence of epilepsy was approximately 1.9 % in all dogs that presented to the teaching hospital (referrals only), and 0.9 and 0.4 % for IdE and StE, respectively. These percentages are similar to previous studies reporting 1–2.6 % for epilepsy in veterinary referral clinics, and 0.5–5 % for IdE in primary clinics [7]. These findings suggest that differences in breeds or countries are not associated with prevalence of epilepsy.…”
Section: Discussionsupporting
confidence: 90%
“…The breeds, Lagotto Romganolo ( LGI2 mutation) [18] and Belgian Shepherd ( ADAM23 mutation) [19], which exhibit genetic epilepsy, were not present in this study. However, 53 dogs (nine breeds) were from the breeds listed as having suspected genetic epilepsy in an IVETF report [7]. …”
Section: Resultsmentioning
confidence: 99%
“…In dogs, the prevalence of epilepsy is estimated to range from 0.5% to 5%. The International Veterinary Epilepsy Task Force (IVETF) reports that idiopathic epilepsy may be the most common form of epilepsy and occurs in up to 75% of epileptic dogs . Temporal lobe epilepsy (TLE) was defined in 1989 by the International League Against Epilepsy as a condition distinguished by recurrent, unprovoked seizures originating from the mesial or lateral temporal lobe .…”
Section: Introductionmentioning
confidence: 99%
“…11 Like in humans, canine epilepsy has been increasing in incidence. 20 Although the increase could be due partially to genetic predisposition and selective breeding-for example, shepherds, retrievers, and terriers have high rates of epilepsy [21][22][23] -epilepsy in dogs is often idiopathic and is not a condition limited to purebred dogs. Lifestyle factors that influence seizures in dogs are similar to those that influence human epilepsy-diet, sleep, exercise, environmental toxins, and in utero environment, among others, 20,23 -and therefore it is important to consider modifiable environmental factors in dogs.…”
Section: Discussionmentioning
confidence: 99%